The Effect of Demographics on Investment Choice: An Empirical Study of Investors in Jammu - Mehta, Sushil Kumar; Aggarwal, Neha (Indian Journal of Finance, 2011)
Behavioral finance is a nascent, but growing discipline, which studies investor’s psychology while making financial decisions. The present study is based on the primary data collected from December, 2009 to March, 2010 in Jammu City. A sample of 120 respondents was taken. The results of the study reveal that there is an association of demographic profiles and personality type of the investor with investment choice. The differences among the different genders are found to be significant for provident funds, fixed deposits, and real estate. The females were found to be conservative while investing, whereas males were found to be aggressive. The investors in the lower age group do not prefer post office as an investment option, but the investors in the higher age group prefer post office as an investment avenue. Most of the investors preferred to consult their family members while making investment decisions and preferred to invest for 1 to 5 years. Most of the investors invest for the safety of money. They are not that concerned for the growth of the money or liquidity. There is no association of income, age, gender, occupation, education on the percentage of income an investor wants to save for the future requirements. There is also no association of age, gender, occupation, education with the appropriate investment period, but there is a significant relationship of income with the appropriate investment period.